Impact des barrières linguistiques sur la sécurité des patients et la qualité des soins. Rapport final - Bowen, Sarah (Société Santé en français, 2015)

The impact of language barriers on patient safety and quality of care. Final report - Bowen, Sarah (Société Santé en français, 2015)

Identification des communautés anglophones du Québec : approche populationnelle dans le cadre de l’évaluation des disparités de santé associées à l’infarctus du myocarde - Drouin, Catherine; Courteau, Josiane; Orzanco, Maria Gabriela; Leroux, Denis; Vanasse, Alain (Revue d’études des Cantons-de-l’Est, 2011)
Il existe peu de données probantes permettant d’évaluer les disparités en matière de santé entre les groupes linguistiques au Québec. Ce projet propose une méthode de classification des communautés du Québec en fonction de l’appartenance linguistique de la population ainsi que l’association, basée sur le lieu de résidence des patients, des données médico-administratives et de celles du recensement. Ensuite, des comparaisons entre les groupes linguistiques quant aux traitements et au suivi des cas d’infarctus du myocarde, réalisées à l’aide de tests du Khi carré, permettent d’identifier que la principale disparité se manifeste dans les taux de revascularisation.

Frontières linguistiques et culturelles : le cas de l’accessibilité aux services de santé et de services sociaux pour la population anglophone de la région de Québec - Hanrahan, Louis; Cloutier, Annabelle; Walling, Richard (Cahiers de l’ÉDIQ, 2016)

Language barriers: Use of regular medical doctors by Canada's official language minorities - Ngwakongnwi, Emmanuel; Hemmelgarn, R., Brenda; Musto, Richard; King-Shier, Kathryn M.; Quan, Hude (Canadian Family Physician, 2012)

Accès interrégional aux services sociaux et de santé pour les personnes d’expression anglaise de l’est de Québec - Richardson, Mary; Gagnon, Hélène (Committee for Anglophone Social Action et Partenaires communautaires Jeffery Hale, 2015)
Cette étude visait à mieux comprendre ce que vivent les anglophones des régions de l‘est du Québec qui doivent se déplacer vers des centres urbains pour recevoir des services de santé spécialisés.

Exploring the determinants of language barriers in health care (LBHC): Toward a research agenda for the language sciences - Segalowitz, Norman; Kehayia, Eva (The Canadian Modern Language Review, 2011)
There is growing interest in language barriers in health care (LBHC) – interest, that is, in how the quality of health care service delivery might be compromised when patients and health care providers do not share the same first language. This article discusses LBHC as an emerging research area that provides valuable opportunities for researchers in various branches of the language sciences – including, among others, applied linguistics, theoretical linguistics, psycholinguistics, second language acquisition – to conduct basic research and to make contributions to the socially important area of medical communication. This article also proposes a research agenda aimed at attracting general language researchers to the study of LBHC, an agenda that is theory driven, programmatic, problem-solving oriented, and interdisciplinary in scope. In proposing this agenda, selected examples have been reviewed from the current literature that can serve as illustrative models for how future research into LBHC can proceed.

Enjeux des services sociaux et de santé en contexte bilingue ou multilingue national. Revue de littérature - van Kemenade, Solange; Forest, Mariève (Secrétariat national du Consortium national de formation en santé, 2015)

Construction of Francophone families’ health literacy in a linguistic minority situation - Zanchetta, Margareth. Santos; Kaszap, Margot; Mohamed, Mohamed; Racine, Louise; Maheu, Christine; Masny, Diana; Cèsar, Ines; Maltais, Claire; Sangwa-Lugoma, G.; Lussier, Nancy; Kinslikh, Diana (Alterstice, 2012)
With the increase in international mobility, healthcare systems should no longer be ignoring language barriers. In addition to the benefit of reducing long‐term costs, immigrant‐friendly organizations should be concerned with mitigating the way language barriers increase individuals’ social vulnerabilities and inequities in health care and health status. This paper reports the findings of a qualitative, exploratory study of the health literacy of 28 Francophone families living in a linguistic‐minority situation in Canada. Analysis of interviews revealed that participants’ social vulnerability, mainly due to their limited social and informational networks, influenced the construction of family health literacy. Disparities in access to healthcare services could be decreased by having health professionals’ work in alliance with Francophone community groups and by hiring bilingual health professionals. Linguistic isolation and lack of knowledge about local cultural organizations among Francophone immigrants were two important findings of this study.